Правові засоби забезпечення реалізації функцій грошей - Царьова, Людмила Кузьмівна; Царева, Людмила Кузьминична; Careva, Ljudmila (My University, 2009)
In t h e article c a t e g o r y » m o n e y » as t h e m o s t i m p o r t a n t e l e m e n t of e c o n o m y is researched, functions of m o n e y as economic and financial category and legal influence of a s t a t e on its executing is are analyzed.
Царьова Л. К. Правові засоби забезпечення реалізації функцій грошей / Л. К. Царьова // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 312-322.
Keywords: гроші; функції грошей; засіб обігу; засіб платежу; засіб накопичення; міра вартості; стабільність національної валюти; правове забезпечення функцій грошей; деньги; функции денег; средство обращения; средство платежа; средство накопления; мера стоимости; стабильность национальной валюты; правовое обеспечение функций денег; money; functions of money; medium of exchange; mean for payment; mean for assimilation; measure of price; national money stability; legal providing of money functions